ANATOMI DAN IDENTIFIKASI SEPULUH JENIS KAYU DARI SULAWESI UTARA - Y I Mandang (Jurnal Penelitian Hasil Hutan, 1992)
Gross  and anatomical features of ten wood species from North Sulawesi were observed and described. Two of them hove light colour and considerable hard, and therefore recommended for ramin substitute. They are Pangium edule and Neonauclea sp.For  identification   purposes  several  important  features  were  noted:  oil  cell  in  Elmerillia,  perforation  plate scalariform  in Elmerillia  and  Laplacea,  vertical septum  in axial parenchima  strand  of Serianthes,  fiber septate in Pangium, Aglaia and Desoxylum.Serianthes minahassae contain fiber with best quality. It is therefore recommended for pulpwood.